O29 Aberrant expression of BMP8A and the BMPRs involves in the progression of breast cancer. (30th July 2021) - Sui, L J; Sanders, A; Jiang, W G; Ye, L
Abstract: Introduction: Role of Bone morphogenetic protein 8A (BMP8A) and BMP receptors (BMPRs) in the tumourigenesis and progression of breast cancer remains elusive. Present study aims to investigate the expression of BMP8A and related BMPRs in breast cancer and their clinical implication. Method: Expression of BMP8A and BMPRs was analysed using the RNA sequencing data of the TCGA breast cancer cohort. Findings were further validated in a meta gene array dataset (E-MDTA6703, n = 2302). STRING dataset was applied to explore the predicted receptors of BMP8A. Clinical relevance of deregulated BMP8A and BMPRs in breast cancer was assessed using both ANOVA and Kaplan-Meier tests. Correlation with markers of proliferation and invasion was evaluated using Spearman test. Result: Analysis of datasets revealed that BMP8A and BMPR1B were highly expressed in breast cancer while ACVRL1, ACVR1, BMPR1A, ACVR1C, TGFBR2, TGFBR3, BMPR2 and ACVR2A were lower-expressed compared with normal controls. Expressions of BMPR1B, BMPR1A, BMPR2, ACVR2A and ACVR2B were highly correlated with BMP8A in the breast cancers. Overall survival in the group with higher BMP8A expression was shorter(median= 122.3 months), P = 0.012 compared with lower-expressed group(median = 215.2 months). No significant difference was observed in BMP8A and BMPRs in tumours according to their staging and lymph node involvement. Positive correlations were found between BMP8A and tumour proliferation, EMT, angiogenic markers. Conclusion: BMP8A is increased in breast cancer and correlates with poor prognosis. The highly correlated BMPRs might be involved in the signal transduction of BMP8A to co-regulate BMP responsive genes and cellular functions which is yet to be investigated. Take-home Message: BMP8A is increased in breast cancer and correlates with poor prognosis.